Crenças e expectativas de familiares sobre o futuro de crianças e adolescentes que passaram por transplante renal - Sarah Silva Abrahão (2014)
The objective of this thesis was identify the believes and expectations of the families about the future of the children and adolescents that made a kidney transplant. The research was made between December of 2011 and February of 2012, on Pediatric Kidney Transplant Ambulatory from Clinic's Hospital from Federal University of Minas Gerais. Twelve mothers and one father of these kidney transplant children and adolescents were interviewed, when accompanying them in the treatment. On this study was utilized a semi structural interview with three basic questions about the transplant experience, the post-transplant and the expectation to the adult life of the transplant child. The dates were analyzed in two theorists models: Collective Individual Discourse Analyses and Critical Discourse Analyses. In synthesis, the study shows that the emotional support for the families to deal with a new situation post-transplant has been offered not only by religion, but also by the science, through the professional's health, that help to increase the conviction of a new stagy install in his son's life and in his own family's life. Finally, the families incorporate a dobble responsability: accompany nearly the treatment to don't suffer undesirable interruption and to create strategies that take these children and adolescents to be, gradativity, subject of them own treatment. The study yet stand out how the exchange of experience and interactions that they live on the ambulatory, with the health professionals or with others parents that be there to the same objective, could perform a support paper on the reconstruction of their lives and their hopes.